Use of hazardous barium slag as a supplementary cementitious material in calcium aluminate cement: Evolution of engineering properties and microstructure - Chen-xi Dong; Zhao Duan; Jiang-shan Li; Xin Chen; Wei Zhang; Haitao Cao; Nianqin Wang (Case Studies in Construction Materials)
The disposal of barium slag (BS), a hazardous industrial by-product, presents a significant environmental challenge, particularly because of its potential toxicity and underuse. Because of its thermodynamic history of rapid water quenching at high temperatures, BS exhibits high reactivity and alkali-activation potential, making it a promising supplementary cementitious material (SCM). This study addresses the dual problems of hazardous waste management and the development of low-carbon cementitious materials by investigating the feasibility of partially replacing calcium aluminate cement (CAC) with BS. In this study, incorporating BS at a replacement ratio of up to 20 % improved the fluidity of a CAC slurry by 16 % and increased its 3-d and 90-d unconfined compressive strengths by 2.5 % and 42 %, respectively, compared to pure CAC. The initial and final setting times of the CAC were delayed by 60 % and 30 %, respectively, which would be beneficial for construction applications requiring extended workability. Microstructural analysis revealed that BS accelerated the hydration process and significantly altered hydration product compositions. The presence of stable hydration products, such as C2ASH8 and AFm phases, reduced the formation of less durable C3AH6, thereby enhancing both early performance and long-term durability. Leaching tests confirmed that Ba²⁺ ions were effectively immobilised within the hydration matrix, ensuring the environmental safety of CAC–BS composites. This study advances the sustainable use of BS and contributes to the development of low-carbon cementitious materials with improved performance and environmental safety. The findings hold significant industrial relevance by promoting resource-efficient construction materials and addressing global industrial by-product challenges, thereby contributing to the circular economy and environmental sustainability.